2019
DOI: 10.1016/j.celrep.2019.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of WDR5 from Chromatin by a WIN Site Inhibitor with Picomolar Affinity

Abstract: SUMMARY The chromatin-associated protein WDR5 is a promising target for pharmacological inhibition in cancer. Drug discovery efforts center on the blockade of the “WIN site” of WDR5, a well-defined pocket that is amenable to small molecule inhibition. Various cancer contexts have been proposed to be targets for WIN site inhibitors, but a lack of understanding of WDR5 target genes and of the primary effects of WIN site inhibitors hampers their utility. Here, by the discovery of potent WIN site inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
173
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(211 citation statements)
references
References 62 publications
9
173
1
Order By: Relevance
“…Gene ontology analyses revealed that most APC/C WDR5 target genes encode proteins involved in ribosome function (GO:0003735, p=1.2×10 −56 ) and mRNA translation (GO:0006413, p=2.2×10 −59 ). These genes are among the very first to be expressed upon mitotic exit 4 , dependent upon WDR5 and MYC 6 , 28 . Accordingly, APC/C WDR5 -target genes were strongly bound by the stem cell transcription factors MYC, OCT4, and NANOG ( Fig.…”
Section: Apc/c Acts At Transcription Start Sitesmentioning
confidence: 99%
“…Gene ontology analyses revealed that most APC/C WDR5 target genes encode proteins involved in ribosome function (GO:0003735, p=1.2×10 −56 ) and mRNA translation (GO:0006413, p=2.2×10 −59 ). These genes are among the very first to be expressed upon mitotic exit 4 , dependent upon WDR5 and MYC 6 , 28 . Accordingly, APC/C WDR5 -target genes were strongly bound by the stem cell transcription factors MYC, OCT4, and NANOG ( Fig.…”
Section: Apc/c Acts At Transcription Start Sitesmentioning
confidence: 99%
“…WDR5 has a very discrete pattern of localization on chromatin, with narrow ChIP-Seq peaks that suggest focal recruitment to specific locations at target loci. 3,13 Within PSGs, the majority of these peaks occur just downstream of the transcription start site, and they are highly conserved in disparate cell types, 3 suggesting that both the binding of WDR5 to these genes, and its specific placement within them, is a precise and stably-determined event. Given the pattern of binding, it is entirely possible that placement of WDR5 on chromatin is driven by a sequence-specific DNA binding protein.…”
Section: The Insight: What Win Site Inhibitors Tell Us About Wdr5mentioning
confidence: 99%
“…A strong empirical case can be made that MLL-rearranged leukemia cells are sensitive to WIN site blockade, 3,9 and every indication is that WIN site inhibitors could be developed into effective treatments for MLL cancers. But the precise molecular underpinnings of this sensitivity remain unknown.…”
Section: The Promise: Clinical Utility Of Win Site Inhibitorsmentioning
confidence: 99%
“…Our recent studies have begun to overcome these obstacles. 8,9,10 In our most recent paper, 10 we studied the MYC-WDR5 connection in the context of Burkitt lymphoma, which is driven by a chromosomal translocation that places MYC expression under control of a potent immunoglobulin heavy chain enhancer. We learned that MYC and WDR5 co-bind to a fairly small group of genes that are manifestly connected to protein synthesis, including those encoding more than half of the proteins in the ribosome.…”
mentioning
confidence: 99%
“…In separate studies, 8 we discovered potent small molecule inhibitors against a second site on WDR5 known as the "WIN (WDR5-interaction) site" 6 ( Figure 1). WIN site inhibitors were originally discovered with the intention of treating leukemias bearing MLL1 gene rearrangements, and every indication is that they will have utility in that context.…”
mentioning
confidence: 99%